Alemtuzumab CARE-MS I 5-year follow-up: Durable efficacy in the absence of continuous MS therapy. (12th September 2017) - Havrdova, Eva; Arnold, Douglas L.; Cohen, Jeffrey A.; Hartung, Hans-Peter; Fox, Edward J.; Giovannoni, Gavin; Schippling, Sven; Selmaj, Krzysztof W.; Traboulsee, Anthony; Compston, D. Alastair S.; Margolin, David H.; Thangavelu, Karthinathan; et al.
Abstract : Objective: To evaluate 5-year efficacy and safety of alemtuzumab in treatment-naive patients with active relapsing-remitting MS (RRMS) (CARE-MS I; NCT00530348). Methods: Alemtuzumab-treated patients received treatment courses at baseline and 12 months later; after the core study, they could enter an extension (NCT00930553) with as-needed alemtuzumab retreatment for relapse or MRI activity. Assessments included annualized relapse rate (ARR), 6-month confirmed disability worsening (CDW; ≥1-point Expanded Disability Status Scale [EDSS] score increase [≥1.5 if baseline EDSS = 0]), 6-month confirmed disability improvement (CDI; ≥1-point EDSS decrease [baseline score ≥2.0]), no evidence of disease activity (NEDA), brain volume loss (BVL), and adverse events (AEs). Results: Most alemtuzumab-treated patients (95.1%) completing CARE-MS I enrolled in the extension; 68.5% received no additional alemtuzumab treatment. ARR remained low in years 3, 4, and 5 (0.19, 0.14, and 0.15). Over years 0–5, 79.7% were free of 6-month CDW; 33.4% achieved 6-month CDI. Most patients (61.7%, 60.2%, and 62.4%) had NEDA in years 3, 4, and 5. Median yearly BVL improved over years 2–4, remaining low in year 5 (years 1–5: −0.59%, −0.25%, −0.19%, −0.15%, and −0.20%). Exposure-adjusted incidence rates of most AEs declined in the extension relative to the core study. Thyroid disorder incidences peaked at year 3 and subsequently declined. Conclusions: Based on these data, alemtuzumab provides durable efficacy through 5 years in the absence of continuous treatment, with most patients not receiving additional courses. ClinicalTrials.gov identifier: NCT00530348; NCT00930553. Classification of evidence: This study provides Class III evidence that alemtuzumab durably improves efficacy outcomes and slows BVL in patients with RRMS.